2007
DOI: 10.1007/s11172-007-0310-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of carbosilane dendrimers of the seventh and ninth generations with terminal butyl groups in the temperature range from T → 0 to 600 K

Abstract: Temperature dependences of the heat capacity of carbosilane dendrimers with butyl termi nal groups of the seventh and ninth generations were determined in the temperature range from 6 to 600 K by precision adiabatic vacuum calorimetry and differential scanning (dynamic) calorimetry. The physical transitions were revealed and their thermodynamic characteristics were analyzed. The experimental data obtained were used to calculate the standard thermo dynamic functions C p (T ), H°(T ) -H°(0), S°(T ), and G°(T ) -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Our choice is determined, first of all, by numerous experimental data collected over the past 10 years on these systems and an unusual behavior reported for high generation dendrimers. In particular, extensive experimental studies of poly­(butyl­carbosilane) dendrimers by various experimental techniques (viscometry, precision adiabatic vacuum and differential scanning calorimetry, small-angle dynamic light scattering, and atomic force microscopy) have shown that increasing dendrimer generation causes a qualitative change of the melt properties. , Namely, while low generation dendrimers demonstrate liquid-like behavior, the high generation dendrimers acquire properties typical for solids. This transition occurs when switching from the sixth to the seventh generation in 3–3 dendrimers (the first number 3 stands for the core functionality while the second number 3 denotes the functionality of the branching points).…”
Section: Introductionmentioning
confidence: 99%
“…Our choice is determined, first of all, by numerous experimental data collected over the past 10 years on these systems and an unusual behavior reported for high generation dendrimers. In particular, extensive experimental studies of poly­(butyl­carbosilane) dendrimers by various experimental techniques (viscometry, precision adiabatic vacuum and differential scanning calorimetry, small-angle dynamic light scattering, and atomic force microscopy) have shown that increasing dendrimer generation causes a qualitative change of the melt properties. , Namely, while low generation dendrimers demonstrate liquid-like behavior, the high generation dendrimers acquire properties typical for solids. This transition occurs when switching from the sixth to the seventh generation in 3–3 dendrimers (the first number 3 stands for the core functionality while the second number 3 denotes the functionality of the branching points).…”
Section: Introductionmentioning
confidence: 99%
“…The rheology of the synthesized compounds in bulk is of particular interest. It has been mentioned above that a transition from a liquid-like to a solid-like behavior was found for non-functional carbosilane dendrimers with butyl-terminated groups upon increasing dendrimer generation [ 29 , 30 , 31 , 32 , 33 , 34 ]. This transition was accompanied by a very strong jump-like rise in melt viscosity [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first intriguing result was obtained several years ago when extensively studying three homologues series of polybutylcarbosilate dendrimers differing in the functionalities of the core and branching Si atoms (3-3, 4-3 and 4-4 dendrimers). Namely, a transition from a liquid-like to a solid-like behavior of carbosilane dendrimer melts was detected, which was expressed as a second transition on the temperature dependence of the heat capacity [ 29 , 30 , 31 , 32 , 33 ]. This qualitative change of the melt properties was demonstrated for all homologues series and it required some explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Smirnova in the Institute of Chemistry of University of N. Novgorod). 33,34 It is important that the appearance of the second transition coincides with the change of the physical state of a dendrimer samples. If till the fifth generation they are viscous transparent liquids, starting from the sixth one they behave as wax-like substances.…”
Section: Carbosilane Dendrimersmentioning
confidence: 99%